2022
DOI: 10.1515/znc-2022-0023
|View full text |Cite
|
Sign up to set email alerts
|

Nitroimidazoles Part 10. Synthesis, crystal structure, molecular docking, and anticancer evaluation of 4-nitroimidazole derivatives combined with piperazine moiety

Abstract: Piperazine-tagged imidazole derivatives 3a (symmetrical di-substituted piperazine) and 5–11 were synthesized through the combination of 4-nitroimidazole derivatives with piperazine moiety. The structural characterization was done by different physical and spectral techniques like NMR (1H and 13C) and mass spectrometry. The constituency of compound 3a was confirmed by X-ray structural analyses. All compounds were assessed for their antiproliferative inhibition potency against five human cancer cell lines namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Some UAE-based studies have demonstrated diverse applications of molecular docking in cancer drug discovery. Al-Soud et al evaluated the anticancer activity of 4-nitroimidazole derivatives [ 52 ], while Amr et al designed peptides targeting lactate dehydrogenase-A [ 53 ]. Mohamady et al created a promising scaffold targeting c-Met and Pim-1 proteins [ 54 ] and Othman et al explored novel phthalimide derivatives [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some UAE-based studies have demonstrated diverse applications of molecular docking in cancer drug discovery. Al-Soud et al evaluated the anticancer activity of 4-nitroimidazole derivatives [ 52 ], while Amr et al designed peptides targeting lactate dehydrogenase-A [ 53 ]. Mohamady et al created a promising scaffold targeting c-Met and Pim-1 proteins [ 54 ] and Othman et al explored novel phthalimide derivatives [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Between 2010 and 2015, over two thirds of the FDA‐approved new molecular anticancer drugs had one or more integrated heterocyclic rings in their structures [6] . Heterocycles such as pyrazole, [7] imidazole, [8] triazine, [9] quinoxaline, [10] and cinnoline [11] are a few instances of those used in cancer treatment. The structure of thiazole consists of a five‐membered ring with atoms of nitrogen and sulfur.…”
Section: Introductionmentioning
confidence: 99%